Readings in Christian ethics ; v. 1 theory and method - Clark, David K.; Rakestraw, Robert Vincent (Grand Rapids, MI Baker, 1994)
Contents : v. 1 : Theory and method.
Includes bibliographical references and index.
Keywords: Christian ethics -- methodology; Evangelicalism